2017
DOI: 10.1186/s13014-017-0864-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive sparing of desktop microbeam irradiation

Abstract: BackgroundNormal tissue toxicity is the dose-limiting side effect of radiotherapy. Spatial fractionation irradiation techniques, like microbeam radiotherapy (MRT), have shown promising results in sparing the normal brain tissue. Most MRT studies have been conducted at synchrotron facilities. With the aim to make this promising treatment more available, we have built the first desktop image-guided MRT device based on carbon nanotube x-ray technology. In the current study, our purpose was to evaluate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The EUD concept was used as an approach to translate the dose distribution of microbeam arc therapy into conventional radiotherapy dose. As the EUD followed the trend of the valley dose, it confirms the observation that normal tissue toxicity depends primarily on the valley dose [2] , [5] , [6] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The EUD concept was used as an approach to translate the dose distribution of microbeam arc therapy into conventional radiotherapy dose. As the EUD followed the trend of the valley dose, it confirms the observation that normal tissue toxicity depends primarily on the valley dose [2] , [5] , [6] .…”
Section: Discussionsupporting
confidence: 80%
“…The biological effects of MRT are not fully understood yet [5] , and it is still unclear if a spatially fractionated target dose is more efficient than a homogeneous target dose [2] . Nevertheless, authors agree that a low valley dose, a high peak-to-valley dose ratio (PVDR), and steep lateral penumbras from the peaks to the valleys are crucial for sparing healthy tissue [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…No acute skin toxicity was observed in mice that were irradiated with doses up to 150 Gy and 15 Gy in MBRT and CRT, respectively (figure 9). In a previous study, we demonstrated the sparing effect of MBRT on normal mice brain tissue post-irradiation, up to 8 months (Bazyar et al 2017). Currently, we are investigating the full extent of normal tissue toxicity, ED50 and TD50 of our technique on different tissues.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, numerous previous studies highlighted the different biological responses observed after MBRT or conventional broad beam irradiation, both in terms of normal tissue tolerance and tumour control [9,12,20,26]. Some relevant results from selected in vivo experiments are compiled in Table 6.…”
Section: Discussionmentioning
confidence: 99%